Mineralogy and PTX relationships of the Archean Hannan South Au-Cu (Co-Bi) deposit, Kalgoorlie, Western Australia: Thermodynamic constraints on the formation of a zoned intrusion-related skarn - Mueller, A.; Lawrance, L.; Muhling, Janet; Pooley, G. (2012)
The Hannan South Au-Cu skarn deposit is located 12 km southeast of Kalgoorlie in the 2.7 Ga Eastern Goldfields Orogen of the Archean Yilgarn Craton, Western Australia. Two epidote-quartz-calcite-magnetite orebodies, controlled by the same reverse fault but separated by 450 m, occur in granodiorite porphyry: an Au-Cu skarn in the southeast (30 vol% calcite) and an Au-Co-Bi skarn in the northwest (5.10 vol% calcite). Both are interpreted as remnants of a single eroded body. Regional and skarn pressure estimates of 400 ± 150 MPa indicate formation at 14 ± 5 km paleodepth. Thermodynamic analysis of the silicate-calcite and oxide-sulfide assemblages constrains the temperature of the H 2O-CO 2 fluid to 480° to 530°C in the proximal SE skarn (0.5 wt% Cu, 0.35 g/t Au, 6 g/t Ag), and to 417° ± 32°C in the more distal NW skarn (<0.1 wt% Cu, 3.5 g/t Au, 1.2 g/t Ag). The oxygen fugacity of the fluid declined with temperature from log fO 2 = -18 to -19 (at 500°C) in the southeast, defined by magnetite + rutile ± hematite and by iron-rich epidote (pistacite = 0.31), to log fO 2 = -24 to -26 (at 415°C) in the northwest, defined by magnetite + rutile ± ilmenite and by low iron epidote (ps = 0.25). The high oxygen fugacity stabilized phengitic muscovite + magnetite and restricted the occurrence of biotite to the NW skarn front. The fugacity of total dissolved sulfur decreased with temperature from log fS 2 =-3 to about log fS 2 = -6.5 buffered by pyrite ± pyrrhotite. In the SE skarn, copper precipitated mainly as intermediate solid solution (iss, Cu = Fe), which exsolved inclusions of sphalerite, galena, and Ag-Bi alloy but retained elevated bismuth (=1,600 ppm) and silver (=1,800 ppm) during cooling and inversion to chalcopyrite. Minor gold and electrum (=60 wt% Ag) precipitated together with chalcopyrite and pyrite. In the more distal NW skarn, fluid cooling and reduction caused the deposition of pyrite, minor cobaltite, native gold, and bismuth minerals leading to the large-scale enrichment of gold (3.5 ppm) and bismuth (130-240 ppm). While the SE skarn contains trace hessite, tetradymite, and aikinite, all stable to at least 540°C, the NW skarn contains abundant bismuth sulfosalts (krupkaite, pekoite, junoite, felbertalite, nuffieldite, cosalite) and tellurosulfides (joseite, aleksite). Cosalite is not stable above 425° ± 25°C. The zoned Hannan South skarn is part of a cluster of intrusion-related Au-Cu and distal Ag-Au-Pb-Zn deposits located within 60 km E to SE of the giant Golden Mile (>1,500 t Au) at Kalgoorlie, and part of a larger genetic group including the diorite-hosted Boddington porphyry skarn deposit (968 Mt at 0.11% Cu and 0.65 g/t Au). © 2012 by Economic Geology.